2020
DOI: 10.3390/cancers12102941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Outbreak on Cancer Patient Care and Treatment: Data from an Outpatient Oncology Clinic in Lombardy (Italy)

Abstract: Lombardy was the first area in Italy to have an outbreak of coronavirus disease 19 (COVID-19) at the beginning of 2020. In this context, cancer has been reported as a major risk factor for adverse outcomes and death, so oncology societies have quickly released guidelines on cancer care during the pandemic. The aim of this study was to investigate the management of cancer patients and oncological treatments during the COVID-19 pandemic and to describe the containment measures performed in our outpatient clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
2
41
0
5
Order By: Relevance
“…A study by Dutch authors showed that, in the Netherlands, 30% of cancer patients experienced changes to their oncology treatment or follow-up [17]. The U.S. study showed a 20%-30% reduction in oncology products during the COVID-19 pandemic, while a study by Italian authors confirmed the pandemic's impact on cancer care, but also that cancer patients are usually strongly motivated to continue cancer treatment despite the pandemic [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dutch authors showed that, in the Netherlands, 30% of cancer patients experienced changes to their oncology treatment or follow-up [17]. The U.S. study showed a 20%-30% reduction in oncology products during the COVID-19 pandemic, while a study by Italian authors confirmed the pandemic's impact on cancer care, but also that cancer patients are usually strongly motivated to continue cancer treatment despite the pandemic [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has had a significant negative impact on cancer diagnosis, with a significant decrease of new cancer diagnoses per general practice, as well as in specialized practices [ 8 ]. Thus, a significant reduction in surgery, as well as in access for oncologic therapies, is the logical consequence of the COVID-19 pandemic [ 9 , 10 ]. Focusing on urologic surgeries, a 67% reduction in oncological procedures could be noticed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the current pandemic, in some hospitals oncological treatments have continued despite the lack of places in intensive care units and surgical theaters due to the high number of severe COVID-19 cases (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%